The pnictogen bond: a quantitative molecular orbital picture - de Azevedo Santos, Lucas; Hamlin, Trevor A; Ramalho, Teodorico C; Bickelhaupt, F Matthias (Physical chemistry chemical physics, 2021)
We have analyzed the structure and stability of archetypal pnictogen-bonded model complexes D3PnA- (Pn = N, P, As, Sb; D, A = F, Cl, Br) using state-of-the-art relativistic density functional calculations at the ZORA-M06/QZ4P level. We have accomplished two tasks: (i) to compute accurate trends in pnictogen-bond strength based on a set of consistent data; and (ii) to rationalize these trends in terms of detailed analyses of the bonding mechanism based on quantitative Kohn-Sham molecular orbital (KS-MO) theory in combination with a canonical energy decomposition analysis (EDA) and Voronoi deformation density (VDD) analyses of the charge distribution. We have found that pnictogen bonds have a significant covalent character stemming from strong HOMO-LUMO interactions between the lone pair of A- and σ* of D3Pn. As such, the underlying mechanism of the pnictogen bond is similar to that of hydrogen, halogen, and chalcogen bonds.